SELF CHARGING ELECTRIC VEHICLE - Prof. Shaikh A. H. A. R.; Mr. Tejas Honmute; Mr. Chaitanya Savant; Mr. Raju Koli; Mr. Tukaram Gurav (International Journal of Innovations in Engineering Research and Technology, 2023)
In this 21st (twenty-first) century conservation of power is the most compulsory phase of the society and as automobile is a paramount phase of society in day to day life, subsequently the conservation of power as properly as pollution due to the utilization of Bio-fuels in vehicle quarter is a difficult job. So strength conservation and pollution free conveyance grew to be most paramount factor. To resolve this trouble the thought of Electric Conveyance (EV) (electricity powered automobile) machine was once introduced, this can be utilized in all kind of automobiles such as cars, bus, truck etc. But as soon as the battery of EV is charged it peregrinates a inhibited distance, once more we have to cost the battery of conveyance, which is a time eating process.. In this paper we worked on this issue of electrical Vehicle (EV). We resolved this by doing parallel operation of battery with self-generation. This will helps to improve the distance covering rang of electrical vehicle (EV) and make it more efficient. It will save the lot of time which is needed to charge the electric vehicle (EV).